Analisa System Usability Scale (SUS) pada Antarmuka Sistem Informasi Belajar Islam Berbasis Web - Didiet Anindita Arnandy; Muhamad Basyrul Muvid; Achmad Arrosyidi (Jurnal Al-Manar, 2023)
One way to stem the notion of radicalism is to use the internet as a learning resource in the form of website creation. The Islamic Learning Information System or abbreviated as SIBI, is a website that provides various kinds of content to learn about Islam. Before developing the website, it is necessary to design an interface so that the website follows the expected target user, especially related to its usability. This study aims to measure the usability of the interface design on the Islamic Learning Information System website using the System Usability Scale (SUS). This study takes data from a survey of lecturers and students at Dinamika University Surabaya and then processes using SUS. The results of the study indicate that the SIBI interface design is quite acceptable to users, but some things still need to be improved further.